2007
DOI: 10.1111/j.1742-1241.2007.01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Why do patients fail HIV therapy?

Abstract: Despite huge advances in terms of the impact of antiretroviral therapy on HIV-related morbidity and mortality patients continue to fail therapy. We discuss the reasons why failure occurs including primary or transmitted resistance, poor adherence, toxicity and drug potency. We performed a review of PubMed, Medline and recent conference abstracts for information on antiretroviral toxicity, adherence, failure and transmitted resistance. Most first-line regimens are now similar in potency and, assuming susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…24,25 Many potentially debilitating adverse effects of ART have also been shown to contribute to irregular taking of the drugs and deliberately stopping of medication by some patients. 26 The results of current study revealed that the side effect of ART was not associated with ART adherence. This could be the reporting of the respondents being experiencing side effects of ART from both optimal and sub optimal adherence groups.…”
Section: Discussionmentioning
confidence: 60%
“…24,25 Many potentially debilitating adverse effects of ART have also been shown to contribute to irregular taking of the drugs and deliberately stopping of medication by some patients. 26 The results of current study revealed that the side effect of ART was not associated with ART adherence. This could be the reporting of the respondents being experiencing side effects of ART from both optimal and sub optimal adherence groups.…”
Section: Discussionmentioning
confidence: 60%
“…Drug interactions with antiretrovirals are therefore not only modulating metabolism and excretion (clearance) of drugs by modulating CYP activity but may also substantially alter drug distribution through modulation of drug transporters (25). Because both mechanisms may immediately translate into changes in drug concentrations, they will also be important for drug failure and the occurrence of viral resistance (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…However, therapy with efavirenz and also HAART in general is complicated by drugdrug interactions (2). Interactions may therefore modify the treatment response by augmenting toxicity or decreasing drug concentrations at the site of action, ultimately causing treatment failure and viral resistance (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…However achieving durable viral suppression in a majority of patients in LMICs remains a challenge, due in part to advanced disease at time of treatment initiation, interruptions in drug supply chain, drug interactions with frequently prescribed medications, and drug toxicities associated with guideline driven antiretroviral regimens. Antiretroviral intolerance and toxicity prevent adherence and predispose patients to fail HIV therapy [4]. In many LMICs faced with limited drug formulary the increased cost and complexity of care created by drug toxicity are additional strains to the health system [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral intolerance and toxicity prevent adherence and predispose patients to fail HIV therapy [4]. In many LMICs faced with limited drug formulary the increased cost and complexity of care created by drug toxicity are additional strains to the health system [4][5][6]. Therefore the subsequent need to improve health providers capacity for early detection and competent management of adverse effects, the resulting need to improve laboratory capacity to detect serious side effects and demand to widen the antiretroviral formulary for appropriate switching of problem drugs further increases the costs of HIV care and treatment [7].…”
Section: Introductionmentioning
confidence: 99%